Food Insecurity, Food Assistance, and Psychological Distress among University Students: Cross-Sectional Survey Western Australia, 2020 - Dana, Liyuwork Mitiku; Wright, Janine; Ward, Rebecca; Dantas, Jaya A R; Dhaliwal, Satvinder; Lawrence, Blake; O’Connor, Moira; Booth, S.; Kerr, Deborah; Pollard, Christina (2023)
University students have been identified as a population sub-group vulnerable to food insecurity. This vulnerability increased in 2020 due to the COVID-19 pandemic. This study aimed to assess factors associated with food insecurity among university students and the differences between students with and without children. A cross-sectional survey of (n = 213) students attending one university in Western Australia measured food insecurity, psychological distress, and socio-demographic characteristics. Logistic regression analyses were conducted to identify factors associated with food insecurity. Forty-eight percent of students who responded to the survey had experienced food insecurity in 2020. International students who were studying in Australia were nine times more likely to experience food insecurity than domestic students (AOR = 9.13; 95% CI = 2.32–35.97). International students with children were more likely to experience food insecurity than international students without children (p < 0.001) and domestic students with (p < 0.001) or without children (p < 0.001). For each unit increase in depression level, the likelihood of experiencing food insecurity increased (AOR = 1.62; 95% CI = 1.12–2.33). Findings show a higher prevalence of food insecurity among international university students and students with children during the COVID-19 pandemic and that food insecurity was associated with higher levels of psychological distress. These findings highlight the need for targeted interventions to mitigate the risk of food insecurity among Australian university students, particularly among international students, students with children, and those experiencing psychological distress.